Stable Bromiranium Ions with Weakly‐Coordinating Counterions as Efficient Electrophilic Brominating Agents. Issue 48 (9th August 2017) - Ascheberg, Christoph; Bock, Jonathan; Buß, Florenz; Mück‐Lichtenfeld, Christian; Daniliuc, Constantin G.; Bergander, Klaus; Dielmann, Fabian; Hennecke, Ulrich
Abstract: Electrophilic halogenating agents are an important class of reagents in chemical synthesis. Herein, we show that sterically demanding bromiranium ions with weakly coordinating counterions are highly reactive electrophilic brominating agents. Despite their high reactivity these reagents are stable, in one case even under ambient conditions and can be applied in electrophilic halogenations of alkenes as well as heteroatoms. Abstract : Strong and stable : Sterically demanding bromiranium ions with weakly coordinating counterions are highly reactive electrophilic brominating agents. Despite their high reactivity these reagents are stable and can be applied in electrophilic halogenations of alkenes as well as heteroatoms.